2004
DOI: 10.1002/hep.20460
|View full text |Cite
|
Sign up to set email alerts
|

Frequent inactivation of the tumor suppressor Kruppel-like factor 6 ( KLF6 ) in hepatocellular carcinoma

Abstract: Hepatocellular carcinoma (HCC) is a leading cause of cancer death worldwide, reflecting incomplete characterization of underlying mechanisms and lack of early detection. Krüppel-like factor 6 (KLF6) is a ubiquitously expressed zinc finger transcription factor that is deregulated in multiple cancers through loss of heterozygosity (LOH) and/or inactivating somatic mutation. We analyzed the potential role of the KLF6 tumor suppressor gene in 41 patients who had HCC associated with hepatitis C virus (16 patients),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
121
4

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 132 publications
(138 citation statements)
references
References 29 publications
13
121
4
Order By: Relevance
“…KLF6 LOH was reported in 36% of 14 informative HCC patient samples and somatic mutations were detected in three patient samples (Wang et al, 2004). These findings complement our original report describing frequent loss and somatic mutation in primary HCC tumor samples (Kremer-Tal et al, 2004). In a separate study, somatic mutations were identified in 8.7% of (Wang et al, 2004).…”
supporting
confidence: 84%
See 1 more Smart Citation
“…KLF6 LOH was reported in 36% of 14 informative HCC patient samples and somatic mutations were detected in three patient samples (Wang et al, 2004). These findings complement our original report describing frequent loss and somatic mutation in primary HCC tumor samples (Kremer-Tal et al, 2004). In a separate study, somatic mutations were identified in 8.7% of (Wang et al, 2004).…”
supporting
confidence: 84%
“…Functional inactivation of the KLF6 gene occurs through several mechanisms, including loss of heterozygosity (LOH), somatic mutation and/or increased alternative splicing that yields a dominantnegative splice isoform, KLF6-SV1. KLF6 dysregulation has been demonstrated in a number of human cancers including prostate (Narla et al, 2001;Chen et al, 2003), colorectal , non-smallcell lung (Ito et al, 2004), gastric (Cho et al, 2005), nasopharyngeal (Chen et al, 2002), hepatocellular (Kremer-Tal et al, 2004) and ovarian carcinomas (DiFeo et al, 2006b) as well as glioma (Jeng et al, 2003). Furthermore, decreased KLF6 mRNA expression is associated with reduced patient survival in prostate (Singh et al, 2002;Glinsky et al, 2004) and lung cancers (Kettunen et al, 2004).…”
mentioning
confidence: 99%
“…In contrast with the other studies, they only analyzed exon 2. None of the other studies included methods to [10][11][12][13] (ranging between 0 and 15%) and colorectal carcinoma [14][15][16][17][18] (ranging between 0 and 44%). Similar to prostate cancer, the first studies conducted on these other tumors indicated a high frequency of mutation, but this was not reproduced in subsequent reports.…”
Section: Discussionmentioning
confidence: 99%
“…9 The reported frequency of KLF6 mutations in different types of human cancer varies in the different published studies. [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] In prostate cancer, four studies have analyzed the frequency of KLF6 mutations. 6,[30][31][32] In the first published study, Narla et al 6 showed a very high frequency, 55%, whereas in the following study, Chen et al 30 obtained a lower frequency, around 15%.…”
mentioning
confidence: 99%
“…[2][3][4] Other mutated genes such as SMAD2/SMAD4 in the transforming growth factor beta (TGF-β) pathway, caspase 8 (CASP8), and Kruppel-like factor 6 were identified with mutation frequency around 10% in HCC, [5][6][7] while most other mutated genes were identified with relatively low frequency of < 10% in HCC. [2] Germline mutations in the TP53 gene have been identified in patients with Li-Fraumeni syndrome, which is an inherited cancer predisposition syndrome characterized by a wide spectrum of neoplasms.…”
Section: Somatic Mutationmentioning
confidence: 99%